Estrada, Oswaldo y Carlos Villacorta, (eds) (2023). Vivir la violencia en el Perú del nuevo milenio. Ediciones MYL - César Ruiz Ledesma (América sin Nombre)
Reseña de César Ruiz Ledesma: Estrada, Oswaldo y Carlos Villacorta, (eds) (2023). Vivir la violencia en el Perú del nuevo milenio. Ediciones MYL. 335 pp. ISBN 978-612-50-1327-9